Evaluación de la eficiencia de un sistema de riego por aspersión instalado en la finca los manzanos, barrio Saucesito, parroquia Mangahurco, cantón Zapotillo - Romero Rueda, Deivar Ariel (2023)
In the "Los Manzanos" farm of the Saucesito neighborhood belonging to the Mangahurco parish, Zapotillo canton, Loja province, the evaluation of the same efficiency and uniformity of the sprinkler irrigation system that has 0.8 ha was carried out. In order to demonstrate and analyze the current situation of said irrigation system, because farmers in this area have observed that this type of irrigation has not been improved for the development of their crops and in order to help and contribute. to the necessary improvements of this. The methodology to follow was first to carry out an inspection of each one of the components of the irrigation system and then continue with the topographic survey that determines the irrigation surface and lengths of the conduction and distribution networks, then the measurement was carried out. of flows with the help of the flowmeter to be able to determine the efficiency of the irrigation system, in terms of distribution uniformity, it was carried out by collecting the flows of the emitters and measuring the pressure with a glycerin manometer, in the same way a manual is made of operation and maintenance so that the farmer has an adequate management of irrigation and therefore, improves the yield of his crop. As a result, that the system is in poor condition, it was possible to determine that there were failures in the pipes. Regarding the uniformity of water application, it is very low, 34,72 %, which does not reach the uniformity standards, in the same way, therefore it affects efficiency, with 27,39 %, these values obtained will be the cause of low yield, since the lack of water is detrimental to the development of crops. According to the results, a redesign proposal was made with the purpose of improving the system, considering, among other parameters, the direction of the slope of the land, a fundamental factor to be considered in the evaluation. Coming to the conclusion that the irrigation system can be improved by up to 75% the uniformity that would be within the required parameters, for which the cost of the redesign is $3,401.92. Keywords: Irrigation uniformity, irrigation system evaluation, sprinkler irrigation, irrigation management.